The Effect of Promotion and Store Atmosphere on Purchasing Decisions - Nurika, Intan; Junaida, Erni; Bulan, T. Putri Lindung (Journal Of Accounting Management Business And International Research, 2023)
This study aims to determine the effect of promotion and store atmosphere on purchasing decisions at Toko Mas Indah, Langsa City. A sample of 96 respondents. The analytical method uses multiple linear regression, t test, F test and coefficient of determination test. The results of the t test state that promotional factors have a significant influence on purchasing decisions and store atmosphere has a significant influence on purchasing decisions. The results of the F test show that promotions and store atmosphere have a significant effect on purchasing decisions. The results of the coefficient of determination test (adjusted R2) obtained a value of 0.737 or 73.7%, this means that promotional variables, store atmosphere and service quality influence purchasing decisions. While the remaining 26.3% is influenced by other variables not examined in this study.